What is the value of sell-side analysts? Evidence from coverage changes – A discussion - Hansen, Robert S. (Journal of Accounting and Economics, 2015)
Li and You (this volume) study public firms’ common stock return reactions to two events: when analysts’ initiate coverage of the firm and when they terminate coverage. They test the returns for evidence of three sources of value added by analysts: (1) more monitoring of the firm, (2) reduced information asymmetry about the firm, and (3) greater demand for the firm’s common stock. They find consistent support for analysts adding value by increasing demand, but not monitoring or by reducing information asymmetry. Their findings also indicate that analysts’ initiations supply little new information. I review these findings, put them in perspective with related research, and note research directions.